Serum estrogenicity and biological responses in African catfish raised in wastewater ponds in Ghana - Asem-Hiablie, S.; Church, C.D.; Elliott, H.A.; Shappell, N.W.; Schoenfuss, H.L.; Drechsel, Pay; Williams, C.F.; Knopf, A.; Dabie, M.Y. (Elsevier, 2013)
Reuse of wastewater for aquaculture improves the efficient use of water and promotes sustainability but the potential effects of endocrine disrupting compounds including estrogens in wastewater is an emerging challenge that needs to be addressed. We examined the biological effects of wastewater-borne estrogens on African catfish (Clarias gariepinus) raised in a wastewater stabilization pond (WSP) of a functioning municipal wastewater treatment plant, a wastewater polishing pond (WWP) of a dysfunctional treatment plant, and a reference pond (RP) unimpacted by wastewater, located in Ghana. Measurements of estrogen concentrations in pond water by liquid chromatography/tandem mass spectrometry showed mean 17 s-estradiol concentrations were higher in the wastewater ponds (WWP, 6.6 ng/L ? 2.7 ng/L; WSP, 4.9 ng/L ? 1.0) than the reference (RP, 3.4 ? 1.1 ng/L). Estrone concentrations were found to be highest in the WSP (7.8 ng/L ? 1.7) and lowest in the WWP (2.2 ng/L ? 2.4) with the RP intermediate (4.7 ? 5.0). Fish serum estrogenicity assayed by ESCREEN was significantly higher in female vs. male catfish in the RP and WSP but not in the WWP (p = 0.05). Histological examination of liver and gonad tissue showed no apparent signs of intersex or pathology in any ponds. The similarities in various measures of body indices between fish of this study and African catfish from other freshwater systems suggest that aquaculture may be a suitable reuse option for treated municipal wastewater.